Product Design Of Film Dental Holder 'Bitewing' For Anterior Dental Radiography - Nursama Heru Apriantoro; Mayarani Mayarani; Ita Astit Karmawati Astit Karmawati (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2017)
Dental radiography conventional examination uses to films being placed into the oral cavity using a finger as the holder. This causes of inconvenience factor and there is primary radiation dose which directing to unnecessary organs especially the hands. The purpose of making the film holder design is to provide a sense of patients comfort and safety from radiation hazards and also to make an alternative tool for dental holders. This study is to make product design, it was conducted of 20 samples at the District Hospital Jakarta and Depok Hospitals using a simple random sample during of July to August 2016. Statistical analysis was performed by a questionnaire with Likert scale. To test the difference between artificial tools and standard film holder Kerrhawe was conducted using test t. The result was obtained there no significant differences between both of them t test > t table, df= 19 and P> 0.05. The test results of benefits using artificial dental holder of bitewing there is no problem and can be accepted by the user